The Effect of Oxidative Stress on Growth and Antioxidant Activity of Microalgae Oocystis sp - Eva Musifa; Mega Warni; Ramanisa Muliani Talib; Abdi Dharma; Elida Mardiah; Yuniar Harvianti; Indah Indah; Alinda Tania (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
This study was conducted to see the effect of growth and antioxidant activity of microalgae Oocystis sp before and after adding NaOCl to Growmore medium combined with urea. Antioxidant activity test was conducted by calculating IC50 spectrophotometrically with the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. Oocystis sp extract was obtained by sonication and maceration process with methanol solvent. The results showed the best growth curve for the growth of microalgae Oocystis sp in a mixture of Growmore medium 0.02% b/v and Urea 0.002% b/v. These results also showed a decrease in Oocystis sp growth in a mixture of Growmore medium 0.02% b/v and Urea 0.002% b/v with the lowest growth decrease in the addition of NaOCl with a concentration of 0.01%. The IC50 value of Oocystis sp extract in methanol solvent has high antioxidant activity in Growmore 0.02% b/v + Urea 0.002% b/v medium, which is 55.5862 mg/L. It can be concluded that NaOCl affects the growth and antioxidant activity of microalgae Oocystis sp, but at certain concentrations NaOCl experienced a negative effect.Keywords: Microalgae, Oocytis sp, Oxidative Stress, Growth, Antioxidant